Culinary tourism and architectural heritage in Malang and Binondo: integrating heritage conservation and gastronomic identity through the tourism competitiveness model - Andini Risfandini; Cherylyn Battung Concepcion; Maria Vio Bianca Fernandez Yumikura; Nappy L. Navarra (Jurnal Pariwisata Pesona, 2026)
Culinary tourism has emerged as a strategic avenue for strengthening destination competitiveness by integrating cultural identity, heritage conservation, and experiential value. This study aims to explore the interplay between culinary tourism and architectural heritage in Malang City, Indonesia, and Binondo District, Manila, Philippines, through the lens of the Tourism Competitiveness Model (TCM). Using a qualitative comparative approach, the research analyzes how tangible heritage (historic urban fabric and colonial-era architecture) and intangible heritage (culinary traditions, storytelling, and food practices) interact as core resources, destination management mechanisms, and pull factors within each destination. Findings reveal that Malang’s structured colonial urban planning system, particularly the Bouwplan heritage, enables adaptive reuse of historic spaces for culinary tourism, supported by local governance and community-based initiatives. In contrast, Binondo’s competitiveness is anchored more strongly in its intangible culinary heritage—especially panciteria traditions—amid ongoing challenges of urban congestion and limited formal heritage zoning. Despite differing urban morphologies, both destinations demonstrate that the integration of gastronomic identity with heritage conservation enhances authenticity, visitor engagement, and socio-economic resilience. The study underscores the importance of adaptive reuse policies, heritage-based gastronomic routes, and community participation in sustaining tourism competitiveness. By applying the TCM framework, this research contributes to tourism and heritage literature by illustrating how cities with diverse historical trajectories can strategically align culinary heritage and architectural conservation to support sustainable urban tourism development.